To cool, but not too cool: That is the question - immersion cooling for hyperthermia - Taylor, N. A. S.; Caldwell, J. N.; van den Heuvel, A. M. J.; Patterson, M. J. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Patient coolingtime can impact upon the prognosis of heat illness. Although ice-cold-water immersion will rapidly extract heat, access to ice or cold water may be limited in hot climates. Indeed, some have concerns regarding the sudden cold-water immersion of hyperthermic individuals, whereas others believe that cutaneous vasoconstriction may reduce convective heat transfer from the core. It was hypothesized that warmer immersion temperatures, which induce less powerful vasoconstriction, may still facilitate rapid cooling in hyperthermic individuals.